Intralobar sequestration of lung - Prasad R; Garg Rajiv; Verma Sanjay (Lung India, 2009)
Intralobar pulmonary sequestration is characterized by the presence of nonfunctional parenchymal lung tissue, receiving systemic arterial blood supply. It lacks normal communication with tracheobronchial tree. Failure to diagnose and treat this condition can lead to recurrent pneumonia and fatal hemoptysis. The aim of this case report is to increase awareness about the condition and to review criteria of its definitive diagnosis and subsequent treatment.